The effect of the displacement pressure on migration of fluid during the imbibition for tight oil reservoir - Yubin Yang; Xian Peng; Wenlian Xiao; Qihong Lei; Tao Li; Youan He; Chun Zhang; Jiahao Jiang; Tao Qi; Lingli Zheng; Haoyu Chen (Scientific Reports)
Abstract In recent years, tight oil has emerged as a significant and complex topic in the fields of oil exploration and development. Following hydraulic fracturing, wells are typically shut-in for a designated period to facilitate water uptake into shale formations, which has become the predominant method for developing tight oil resources. During this process, initial pressure—specifically the shut-in pressure post-fracturing—plays a crucial role in ensuring imbibition recovery and determining shut-in duration. This study focuses on the typical terrestrial tight oil found in China—the Chang 7 tight oil from the Ordos Basin. Through quantitative analysis of wettability and pore-throat structure, we elucidate the flow mechanisms of oil during "shut-in" processes under varying pressure differentials using experiments conducted with nuclear magnetic resonance (NMR). Furthermore, we establish a model to quantitatively analyze the relationship between shut-in time and pressure across different reservoir types. Significant variations in wettability were observed among distinct pore spaces. Water-wet pores predominantly occurred within both small and large pores, whereas oil-wet pores were mainly identified in medium-sized pores. During imbibition, fluids initially mobilize crude oil within macropores with an impressive recovery rate reaching up to 25%. This process subsequently transitions into spontaneous sorption dynamics as infiltration continues, leading to reduced recovery rates primarily associated with micropores. Additionally, our findings indicate that the impact of shut-in pressure on enhanced imbibition recovery varies across different reservoir types. When the reservoir physical properties are better (i.e. the micro-fractures are more developed in the reservoirs), higher shut-in pressures correlate with improved imbibition recovery; optimal pressures are determined to be approximately 45 MPa ~ 55 MPa, with corresponding ideal shut-in durations of around 20 ~ 30 days. Conversely, the worse the reservoir physical properties are, we recommended to maintain maximum possible pressures to minimize shutdown periods while reducing ineffective downtime during well operations.